2023
DOI: 10.1101/2023.08.03.551752
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An adaptable, reusable, and light implant for chronic Neuropixels probes

Abstract: Understanding neural processes such as memory formation, learning, or aging requires tracking the activity of neural populations across short and long time scales. Such longitudinal recordings can be achieved with chronically implanted Neuropixels probes. An ideal chronic implant should (1) allow stable recordings of neurons for weeks; (2) be light enough for use in small animals like mice; (3) allow reuse of the probes after explantation. In this initial preprint, we present the "Apollo Implant", an open-sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 54 publications
4
14
0
Order By: Relevance
“…We found that users preferred to use new probes whenever possible and only reused probes later in their experimental journey. The total number of reuses of single probes ( 5) is comparable to the best reported 20 , and we found no meaningful detriment to the recording quality in repeated reuse.…”
Section: Repix Allows Stable Long-term Recording and Reuse Of Probessupporting
confidence: 78%
See 2 more Smart Citations
“…We found that users preferred to use new probes whenever possible and only reused probes later in their experimental journey. The total number of reuses of single probes ( 5) is comparable to the best reported 20 , and we found no meaningful detriment to the recording quality in repeated reuse.…”
Section: Repix Allows Stable Long-term Recording and Reuse Of Probessupporting
confidence: 78%
“…As the Neuropixels recording technology evolved and matured, researchers developed solutions to chronically implanting Neuropixels probes. They have a common design principle using payload and docking modules and have been effectively used for some combination of recording from Neuropixels 1.0; Neuropixels 2.0; in mice or rats; with the ability to reuse probes 3,17,19,20,[23][24][25][26] . Repix combines all these qualities to ensure longterm recordings in an aluminum system that is strong enough for rats and light enough for mice; which can accommodate any probe type; in assays that span rodent behaviors, including freely-moving, head-fixed, and social behaviors; where probes can be reused; all in a solution with a minimal number of components that can be adapted for individual use cases.…”
Section: Repix a Minimalistic Implant System For Neuropixels Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to designing a novel fixture, it was essential to optimize the surgical procedures for multi-probe implants. Chronic surgical procedures are rarely standardized across labs, however certain principles, such as the use of viscous cement to seal the implant leaving the shank open to air, are relatively constant across published work (Bimbard et al, 2023;Jones, 2023;Juavinett et al, 2019;Luo et al, 2020;van Daal et al, 2021). When implanting a single probe, or multiple probes attached to the same fixture, surgeries are reported to take 4-5 hours (van Daal et al, 2021), which would render implanting multiple probes on independent fixtures impractical and time consuming.…”
Section: Resultsmentioning
confidence: 99%
“…Recoverability is possible and is reported for many of the designs; however, the reliability of the process remains largely uncharacterized (Bimbard et al, 2023;Jones, 2023;Juavinett et al, 2019;Luo et al, 2020;van Daal et al, 2021). In detail, Juavinett et al 2019 report 4 explants out of 10 with 2 re-uses.…”
Section: Introductionmentioning
confidence: 99%